Depression is associated with non‐alcoholic fatty liver disease among adults in the United States. Issue 5 (22nd July 2019) - Kim, Donghee; Yoo, Eric R.; Li, Andrew A.; Tighe, Sean P.; Cholankeril, George; Harrison, Stephen A.; Ahmed, Aijaz
Summary: Background: Currently, the relationship between depression and non‐alcoholic fatty liver disease (NAFLD) is not clearly defined. Aim: To determine whether depression is associated with NAFLD and NAFLD‐related advanced fibrosis in a large population sample. Methods: We performed a cross‐sectional analysis using the 2007‐2016 National Health and Nutrition Examination Survey database among adults (20 years or older) in the United States (US). Depression and functional impairment due to depression were assessed with the Patient Health Questionnaire (PHQ‐9). NAFLD was defined by utilising the US fatty liver index (USFLI), hepatic steatosis index (HSI) and the fatty liver index (FLI) in the absence of other causes of chronic liver disease. The presence and absence of advanced fibrosis in NAFLD were defined by Fibrosis‐4 score. Results: Of the 10 484 subjects (mean age 47.0 years; 48.8% men), the prevalence of depression and functional impairment due to depression was higher in subjects with NAFLD than in those without. Compared to subjects without depression, those with depression were 1.6‐2.2‐fold more likely to have NAFLD. In our multivariate analyses, depression_med was associated with increased risk of NAFLD using USFLI (odds ratio [OR] 1.48 95% confidence interval [CI] 1.17‐1.87), HSI (OR 1.51 95% CI 1.04‐2.19) and FLI (OR 2.01 95% CI 1.65‐2.48), respectively. The addition of diabetes, obesity and lipid profile to the model reduced the ORs for depression, but the significance persisted. Depression was not associated with NAFLD‐related advanced fibrosis. Conclusions: In a nationally representative sample of US adults, depression was independently associated with NAFLD.